2019
DOI: 10.3390/polym11121914
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bisphenol A Based Phosphazene-Containing Epoxy Resin with Reduced Viscosity

Abstract: Phosphazene-containing epoxy oligomers (PEO) were synthesized by the interaction of hexachlorocyclotriphosphazene (HCP), phenol, and bisphenol A in a medium of excess of epichlorohydrin using potassium carbonate and hydroxide as HCl acceptors with the aim of obtaining a product with lower viscosity and higher phosphazene content. PEOs are mixtures of epoxycyclophosphazene (ECP) and a conventional organic epoxy resin based on bisphenol A in an amount controlled by the ratio of the initial mono- and diphenol. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…So, it is extremely important to ameliorate the fire safety of EP. At present, the most widely used method is additive flame retardants to improve the flame retardancy 7–10 . However, the low transparency, environmental pollution, or high‐addition amount are the main disadvantages of its application, 11,12 especially for coatings and circuit boards.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is extremely important to ameliorate the fire safety of EP. At present, the most widely used method is additive flame retardants to improve the flame retardancy 7–10 . However, the low transparency, environmental pollution, or high‐addition amount are the main disadvantages of its application, 11,12 especially for coatings and circuit boards.…”
Section: Introductionmentioning
confidence: 99%
“…The other example is hexaphenoxycyclotriphosphazene, which is used as a highly effective flame retardant for a large number of synthetic polymers. A number of effective flame-retarded functional epoxy resins, amine curing agents and benzoxazines with a phosphazene core have been proposed [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Carboxyl-containing epoxyphosphazenes and their use as a catalyst for the polymerization of benzoxazines have also been reported [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arylphosphazenes compared with other organophosphorus compounds, have, as a rule, higher thermal stability and chemical resistance and are promising fire retardants [ 4 , 6 , 13 , 14 ], characterized by the synergistic effect of phosphorus and nitrogen [ 15 ]. Thus, phenoxycyclophosphazenes were commercialized as a flame retardant by Otsuka Chemical et al Recently it was shown that epoxy-amine matrices modified with epoxycyclophosphazene [ 16 ] are characterized by enhanced mechanical properties [ 17 ]. Therefore, epoxy resins modified with epoxycyclophosphazenes appear to be a promising base for halogen-free binders for critical use.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, epoxy resins modified with epoxycyclophosphazenes appear to be a promising base for halogen-free binders for critical use. Recently, scalable methods for epoxycyclophosphazene synthesis have appeared [ 6 , 16 , 18 ], which make it possible to believe that they may become available starting components in the market for composite manufacture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation